Stevia - sweet opportunity - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
The Stevia (Stevia rebaudiana) plant is fast winning a place in the market for sugar-substitute sweeteners in North America, Europe and Japan. A native of Paraguay, it is grown traditionally in South Africa, Madagascar and China. Its medicinal...